STRATEGI PENINGKATAN EFEKTIVITAS PEMANFAATAN LIMBAH ORGANIK MENJADI PUPUK HAYATI DI NAGARI BALAI TANGAH KECAMATAN LINTAU BUO UTARA - Ghina Azzahra; Jefril Rahmadoni; Syahda Permata Ardelia; Selvi Ananda; Muthia Luthfiyah; Dwi Rendra Graha Putra; Andina Juita Sari (Jurnal Hilirisasi IPTEKS, 2024)
According to the Ministry of Environment and Forestry's (KLHK) National Waste Management Information System data for 2022, input results from various districts and cities across Indonesia revealed that the amount of national waste stockpiled had reached 21.1 million tons. Of total national waste production, 65.71% (13.9 million tons) can be managed, while the remaining 34.29% (7.2 million tons) is not well managed. One place that produces a lot of waste is the market. Every Thursday, Nagari Balai Tangah hosts a large market, also known as Balai. This market specializes in food ingredients such as vegetables, fish, and ready-to-eat foods. This, of course, results in a buildup of organic waste each week, especially if there is no clear waste management system. For this reason, waste management is needed which aims to increase the knowledge of the people of Nagari Balai Tangah, North Lintau Buo District, Tanah Datar Regency in utilizing organic waste into environmentally friendly biological fertilizer. This activity employs a material presentation/coaching method as well as a direct demonstration of biological fertilizer production using household and market organic waste. The findings of this activity indicate that producing biofertilizer from organic waste can improve the effectiveness of waste utilization in Nagari Balai Tangah. Aside from that, this activity has the potential to create new job opportunities in the form of a biofertilizer business, which can then be used by all Nagari people of various ages. Apart from that, increasing the knowledge and ability of the people of Nagari Balai Tangah to utilize organic waste and make a positive contribution to the welfare of the people of Balai Tangah.